1987
DOI: 10.1364/ol.12.000272
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of femtosecond pulses in single-mode fibers having higher-order nonlinearity and dispersion

Abstract: Using computer simulations, we examine the effects of higher-order dispersive and nonlinear propagation processes on the spectral and time development of ultrashort, high-intensity pulses propagating in single-mode optical fibers having normal dispersion. Our results indicate that both the cubic-dispersion term and the shock term of the nonlinear Schrödinger equation contribute to asymmetry in the pulse power spectrum and cause highly nonlinear chirp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…However, experiments [22] and numerical studies [84][85][86][87][88] have shown that higher-order dispersion and nonlinearities become increasingly important for propagation of femtosecond pulses, even for fibers shorter than 1 cm. In order to account for the intensity dependence of the group velocity, the conventional NSE should be extended to include a nonlinear correction term involving the time derivative of the pulse envelope, the so-called optical shock term [84]. This means that the part of the pulse that has the highest peak intensity, moves at a lower speed than the low-intensity wings.…”
Section: Fiber Output: Experiments Vs Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experiments [22] and numerical studies [84][85][86][87][88] have shown that higher-order dispersion and nonlinearities become increasingly important for propagation of femtosecond pulses, even for fibers shorter than 1 cm. In order to account for the intensity dependence of the group velocity, the conventional NSE should be extended to include a nonlinear correction term involving the time derivative of the pulse envelope, the so-called optical shock term [84]. This means that the part of the pulse that has the highest peak intensity, moves at a lower speed than the low-intensity wings.…”
Section: Fiber Output: Experiments Vs Numerical Simulationsmentioning
confidence: 99%
“…Significant progress in numerical modelling of pulse propagation in fibers was made by taking into consideration both the optical shock term and higher-order dispersion [84][85][86][87]. It was shown that these two effects acting together suppress severe oscillations in the chirp.…”
Section: Fiber Output: Experiments Vs Numerical Simulationsmentioning
confidence: 99%
“…The positive second order phase due to SPM is cancelled by the negative GVD of the anomalous dispersive FS. Similar approaches to balance the effect of self-steepening during nonlinear propagation in single mode fibers by grating pairs have been discussed already in mid 80's [23,24] and were recently implemented to compensate TOD in an Yb fiber laser oscillator [25]. However, above mentioned schemes were demonstrated with multi-cycle pulses.…”
Section: Methodsmentioning
confidence: 93%
“…When two or more optical fields with different frequencies co-propagate in a fiber, the cross-phase modulation (XPM) will be produced through the optical Kerr effect. When short pulse is considered (nearly 50fs), the third-order dispersion (TOD), which will produce asymmetrical broadening in the time domain for the ultrashort soliton pulses [20], cannot be neglected. Moreover, the higher-order nonlinear effects such as the SS [21] and SFS [22] must be considered.…”
Section: Model and Peregrine Soliton Solutionmentioning
confidence: 99%